STEM Skills Self-efficacy and Motivation: ANALYSIS OF OPPORTUNITIES AND CHALLENGES IN ELEMENTARY LEVEL - Erna Suhartini; Rosita Putri Rahmi Haerani; Nur Hasanah; Anugrah Putri Nur’aini; Nurul Fitriyah Sulaeman; Shelly Efwinda (JURNAL EDUSCIENCE, 2026)
Purpose – The study examines the self-efficacy in STEM skills and the motivation of elementary school student in science learning on the theme of sustainable cities, highlighting gender and regional differences in East Kalimantan to understand the opportunities, challenges, and their implications for inclusive and sustainable learning.Methodology – This study employed a mixed-methods approach with a cross-sectional, explanatory, sequential design, involving 450 students and 8 teachers from elementary schools in Kutai Kartanegara, Samarinda, and Balikpapan. Data were collected through validated self-efficacy and motivation questionnaires and teacher interviews, then analyzed descriptively (SPSS) and thematically using joint display integration to illustrate students' self-efficacy and motivation dynamics across gender and regional contexts. Qualitative findings complemented the quantitative results by capturing teachers’ perspectives on instructional practices and classroom barriers to STEM implementation.Findings – Findings reveal that while students generally demonstrate high levels of self-efficacy and motivation, there is a subtle gap: female students exhibit lower confidence in engineering tasks, mathematical self-efficacy remains moderate across all genders, and little disparity is evident between urban and non-urban learners. Students are highly motivated by activities that are enjoyable, challenging, and hands-on; however, traditional teaching methods and limited adoption of innovative STEM approaches—including project-based and game-based learning—constrain these benefits.Contribution– When supported by differentiated and inclusive learning environments, such approaches enhance self-efficacy, foster critical thinking, and increase engagement. These findings underscore the need for pedagogical transformation in elementary STEM education to address gender and regional gaps while maximizing students’ confidence, motivation, and preparedness for future academic and career pathways.